Using PowerPoint as a Learning Media for Elementary School Students about Personal and Environmental Health - Wirdatul Hayaty; Asep Bayu Dani Nandiyanto (Open Global Scientific Journal, 2022)
This study aims to analyze and measure the effectiveness of using PowerPoint as a learning medium in increasing elementary school students' knowledge of personal and environmental health and increasing students' knowledge of personal and environmental health. The research subjects were 16 minor medical students at SD Negeri 1 Padang Panjang Barat Padang Panjang, West Sumatra, Indonesia. This study uses a learning method by explaining personal and environmental health materials using powerpoint media in which there are also interesting pictures. The students were also given a pre-test before learning started to measure how much students' knowledge of the material was and a post-test after learning was done to find out how much improvement occurred to students. The results showed that when the pretest was carried out there were still many students who did not know about their own health and the environment. After being given learning using powerpoint media accompanied by interesting pictures, there was an increase in students' knowledge about personal health and the environment. The use of powerpoint is also very effective in helping students think and analyze something.